Identification of developmental stages in landscape and technical systems - Лаврик, О. Д. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2017)
The aim of the article is to analyze the development of ideal landscape and technical system, the isolation and characterization of the stages, which will help to identify the stages of the system.Problems of landscape and technical systems stages development were studied by F.M. Mil kov, G.I. Denysyk, Iu.V. Yatsentyuk, I.P. Kozyns ka. In their studies, the authors briefly describe the dynamics of anthropogenic landscapes development, but do not pay attention to the identification of landscape and technical systems stages of development.Scientific research is based on the use of modeling paradigm in geography. The example of an ideal landscape and technical systems shows specific features of development stages.The theoretical results of the paper have a basis for the future development of the techniques of field research of landscape and technical systems.The ability to identify landscape and technical systems stage of development allows for constructive support systems in optimum condition and ensure their long-term operation.The author analyzes the problem identification of landscape and technical systems development stages. Three stages: «genesis», functioning and «destruction» have been allocated. Each stage consists of three phases. Each stage and phase is analyzed in detail. The role of each of the three blocks (natural, technical and control) is explained at a certain stage of its development.Stage of «genesis» is starting. At this stage the design, construction and commissioning of engineering facilities are considered. Between natural and technical units of the system stable relations of matter, energy and information exchange are established.During the functioning stage connection is established between the natural, technical and control units and the category of engineering construction changes in the landscape and technical systems. The system shows signs of the relevant natural area. The phase is characterized by an optimum combination of organic functioning of the three units of the system.Stage of «destruction» is the ultimate in the development of the landscape and technical system and indicates the «aging» and moves into the category of landscape and technogenic systems. At this stage to return the system to its original state a fully functioning control unit should be established.The graph shows the duration of the operational stages in the ideal landscape and technical system of the control unit s activity. It was noted that the landscape and technical system developes in several ways. Certain phases or stages can be skipped and moved on to the next category.